The Model Of Employee Satisfaction : A Human Resources Management Perspective - Lukman hadi; Eddy Irsan Siregar; Siti Hafnidar (DINASTI RESEARCH, 2020)
This study aims to examine and analyze the influence of jobinvolvement, career development, and compensation on job satisfaction. The sampling method uses Proportionate Random Sampling. Data were taken directly using questionnaire with 58 respondents of permanent employees of M2M Solutions Ltd. The method of analysis used in this study is multiple linear regression. The result of the research shows that job involvement has a positive and significant effect on job satisfaction, career development has a significant and positive effect on job satisfaction, compensation has significant and positive effect on job satisfaction. Job involvement, career development, and compensation together have a significant and positive impact on job satisfaction. This means that job satisfaction can be explained by the three independent variables of jobinvolvement (X1), career development (X2), and compensation (X3). From the result of multiple regression test, compensation is the most dominant variable in affecting job satisfaction.